Garis panduan pembangunan media pengajaran berkonsepkan penceritaan digital untuk tablet skrin sentuh - Hashiroh, Hussain (2017)
The usage of the Digital Storytelling (DST) concept for development process in instructional media is not fully comprehended. Besides, the features of DST tools also need to be identified. The lack of standard guidelines to develop instructional media with touch screen interaction should also be addressed. Therefore, this study proposes a guideline for the development of instructional media with DST concept (MPBPD) for touch screen tablet that could help designers to produce compelling MPBPD apps. This study applies the Design Science Methodology to achieve the objectives of the study that comprises of five phases: problem awareness, suggestion, development, evaluation and conclusion. A total of 13 experts and 70 teachers from the Institut Pendidikan Guru (IPG) and a school in the Northern Region, Malaysia participated in the quality evaluation phase using a set of questionnaire called Q-Qguide. Furthermore, 40 MPBPD apps created by the respondents were measured in terms of compellingness using a rubric instrument (R-Compelling). The findings indicate that the guideline is of quality and has positive and high relationship in the dimension of usefulness, ease of use, easy to understand, applicability and tablet interaction. MPBPD apps which were developed by implementing the guideline is found to meet the guideline elements and has a high perceived compellingness level. In conclusion, the study has contributed a guideline for the development of instructional media with DST concept for touch screen tablet